2006
DOI: 10.1515/cclm.2006.247
|View full text |Cite
|
Sign up to set email alerts
|

Clinical chemistry reference values for 75-year-old apparently healthy persons

Abstract: In summary, we have established a reliable set of reference data for hormonal, hematological, and clinical chemistry analytes for elderly subjects. These values will be very useful for our future attempts to correlate disease states and aging processes with metabolic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Fourteen studies [14,19,21,22,30,32,33,35,[37][38][39][40][41][42] implemented the rankbased non-parametric approach recommended by the CLSI although only six [14,30,32,38,40,42] of these studies abided by the minimum requirement of 120 subjects per partition. Six [14,22,30,32,39,40] of the 14 studies also provided confidence intervals for their lower and upper limit estimates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fourteen studies [14,19,21,22,30,32,33,35,[37][38][39][40][41][42] implemented the rankbased non-parametric approach recommended by the CLSI although only six [14,30,32,38,40,42] of these studies abided by the minimum requirement of 120 subjects per partition. Six [14,22,30,32,39,40] of the 14 studies also provided confidence intervals for their lower and upper limit estimates.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported RIs using more than one method [25,46,48,51,52,58]. Only four [22,25,57,59] of the 26 studies provided confidence intervals for their estimates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, "elderly" is taken to mean over 65 years of age, thus, the inclusion criterium of in good agreement with their reference values [8,[10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%